Perancangan Helpdesk Pada Balai Pengelola Kereta Api Ringan Sumatera Selatan - Riski, Muhammad; Purwani, Fenny; Ipandy, Ahkmad (MDP Student Conference, 2024)
The South Sumatra Light Railway Management Center (BPKARSS) which is responsible for transportation services in South Sumatra Province has problems in managing manual complaints, problems, and reports. This study aims to design a helpdesk system using the UML Prototype and Modeling method to improve the efficiency of BPKARSS internal services. The research focused on the design of the helpdesk system as the main solution to handle complaints and reports at BPKARSS, With the UML Prototype and Modeling approach, this design aims to increase responsiveness to employee requests and solve problems quickly and structured. The Prototype method allows identification of design needs and improvements before full implementation, while UML Modeling describes the structure and behavior of the system, The results of this study are in the form of a Prototype Helpdesk design which is expected to overcome obstacles in managing complaints and manual problems at BPKARSS. It is expected that this design will improve the efficiency of handling internal problems with a focus on integrating responsive and structured solutions for employees.